Peran ziswaf dalam mengentaskan kemiskinan dan ketimpangan sosial - Adzkiya, Hida Amalia (Maliki Interdisciplinary Journal, 2025)
This study aims to determine the role of ZISWAF in alleviating poverty and social inequality. Poverty and social inequality are still major challenges in many countries, including Indonesia, although various policies and programs have been implemented. One potential solution that can overcome this problem is through the ZISWAF instrument (Zakat, Infaq, Sedekah, and Wakaf), which is based on social solidarity and sharia principles. ZISWAF functions as a means of distributing wealth that flows from the wealthy to the needy, as well as a means of economic empowerment, education, and health. To collect data, we used the literature study method. Data were collected from valid online sources, including journals, books, and previous research results. The analysis is presented in the form of descriptive narratives. Based on this study, ZISWAF has great potential, but its management must be carried out with transparency, accountability, and adequate education to the community in order to achieve its goals optimally. With proper utilization, ZISWAF can be an instrument that not only addresses the problems of poverty and social inequality, but also contributes to sustainable socio-economic development, creating a more just and prosperous society.